Using the APAIS Score for Preoperative Anxiety of Anesthesia Evaluation Among Adult Patients at Hillah Teaching Hospitals - Al-Shammari, Moustafa A. (Scientific Journal of Medical Research, 2024)
Background: Patients’ preoperative anxiety is a considerable concern, with potential implications for emotional, psychological, and physical well-being. Identifying and understanding anxiety levels are crucial for providing effective support. This study explores the impact of patient demographics, including age, gender, type of operation, surgical procedure, suggested anesthesia type, and prior anesthesia experiences on preoperative anxiety. Material & Methods: In the operation units of three adult hospitals in Hillah City, Babylon Province, a descriptive cross-sectional study was carried out from October 2021 to April 2022. The study aims to investigate the effects of preoperative anxiety on patient demographics, including age, gender, type of operation, surgical procedure, suggested anesthesia type, and previous anesthesia experiences. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) was used as an evaluation instrument during interviews with 115 patients. Results: Out of the 306 individuals, 115 fulfilled the requirements for inclusion, and the average APAIS score was discovered to be 23.34 ± 4.709. Age and the sub-scores for the demand for knowledge showed a significant negative correlation (r: -0.160; p = 0.037) for observation. According to the survey, those with lower educational levels—such as those who cannot read or write—had lower results than college graduates (14.60 ± 3.502), elementary school graduates (13.75 SD ± 5.257), and secondary school graduates (12.33± 5.680). In addition, females showed considerably higher sub-scores for the thirst for information than did males (p = 0.028). Compared to patients who chose general anesthesia, those who had regional anesthesia reported better overall ratings (p = 0.038). Conclusions: understanding patient anxiety and providing tailored responses can improve patient satisfaction and outcomes. The APAIS might improve preoperative consultations as it is a useful tool for evaluating anxiety before to surgery. It may be possible to improve patient experiences and overall results by including this tool in the preoperative procedure.